Impingement of the Thyroid Cartilage on the Carotid Causing Clicking Larynx Syndrome and Stroke. (26th November 2021) - Han, Catherine Y.; Long, Sallie M.; Parikh, Neal S.; Phillips, C. Douglas; Obayemi, Adetokunbo; Yu, Victoria X.; Banuchi, Victoria
Abstract : We present the case of a patient with a recent history of ischemic stroke who presented with clicking larynx syndrome, a condition in which clicking noises in the larynx can be provoked by movement of the head and neck. Diagnostic imaging revealed unusual development and posterior angulation of the superior horn of the thyroid cartilage that potentially was causing trauma to the left common carotid artery. We deduced that symptomatic impingement of the carotid artery by the thyroid cartilage was not only the cause of the patient's clicking larynx syndrome, but also suspected to be the cause of her prior strokes due to repetitive trauma resulting in thrombus. The patient was managed surgically with thyroplasty and transcervical resection of the left greater cornu of the thyroid cartilage with resolution of her symptoms. Anatomical displacement of the thyroid cartilage can manifest as clicking larynx syndrome as well as cause mechanical injury to the carotid artery, resulting in turbulent flow, possible thrombosis, and stroke. Laryngoscope, 132:1410–1413, 2022